1997
DOI: 10.1200/jco.1997.15.4.1617
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-macrophage colony-stimulating factor/interleukin-3 fusion protein versus granulocyte-macrophage colony-stimulating factor after autologous bone marrow transplantation for non-Hodgkin's lymphoma: results of a randomized double-blind trial.

Abstract: There was a trend toward a slight improvement in neutrophil engraftment post-ABMT with the PIXY321 administered by an SC route compared with GM-CSF administered by an IV route. However, no differences could be identified between the two agents with respect to the time to platelet transfusion independence. Patient, regimen, and graft characteristics were most predictive of the engraftment tempo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…[51][52][53][54] However, PIXY-321 (an IL-3/GM-CSF fusion protein) had little impact on platelet transfusion requirements after transplantation. 55 Sequential IL-3/ GM-CSF (IL-3 doses Յ 1 g/kg per day) also has been tested in a small group of patients with MDS (n ϭ 9 patients). 56 A clinically relevant response was seen in only one patient with thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53][54] However, PIXY-321 (an IL-3/GM-CSF fusion protein) had little impact on platelet transfusion requirements after transplantation. 55 Sequential IL-3/ GM-CSF (IL-3 doses Յ 1 g/kg per day) also has been tested in a small group of patients with MDS (n ϭ 9 patients). 56 A clinically relevant response was seen in only one patient with thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…[136] The fusion protein PIXY321 is significantly more potent than either GM-CSF or IL-3 alone or in combination in stimulating the in vitro growth of erythroid, monocyte, granulocyte and megakaryocyte progenitor cells. [137] However, in a phase III study comparing PIXY321 administration and GM-CSF administration in adults, [138] and in 2 studies with children, [92,139] no significant advantages were found for PIXY321. Although PIXY321 is not currently being manufactured, it is a good example of the elusiveness of demonstrating the clinical effectiveness of HGFs despite a good scientific rationale and encouraging phase I results.…”
Section: Other Colony-stimulating Factorsmentioning
confidence: 93%
“…In late clinical trials, PIXY321 improved neutrophil engraftment but not platelet mobilization compared with GM-CSF treatment in bone marrow transplantation for non-Hodgkin's lymphoma (52) (32). Reduced megakaryocytopoiesis associated with chemotherapy was often clinically insignificant because of the low platelet threshold required to prevent bleeding (52).…”
Section: Gm-csf and Il-3 Fusion Proteinmentioning
confidence: 99%
“…Reduced megakaryocytopoiesis associated with chemotherapy was often clinically insignificant because of the low platelet threshold required to prevent bleeding (52). The cost of production of PIXY321 and lack of additional clinical or economic advantage over GM-CSF halted further development of this unique molecule.…”
Section: Gm-csf and Il-3 Fusion Proteinmentioning
confidence: 99%